Mortuary practices in the process of Levantine neolithisation - Koutsadelis, Constantinos (Oxford Hedges, 2007)
Mortuary practices: theoretical and methodological framework -- The pre-pottery neolithic in the Levant: a general framework -- Mortuary practices in the pre-pottery neolithic Levant: the archaeological evidence -- The pottery neolithic cultures of the late seventh millennium BC Levant: general framework and mortuary evidence -- Mortuary practices in the pre-pottery neolithic Levant: interpretative approaches -- Mortuary practices in the pottery neolithic
Mortuary practices: theoretical and methodological framework -- The pre-pottery neolithic in the Levant: a general framework -- Mortuary practices in the pre-pottery neolithic Levant: the archaeological evidence -- The pottery neolithic cultures of the late seventh millennium BC Levant: general framework and mortuary evidence -- Mortuary practices in the pre-pottery neolithic Levant: interpretative approaches -- Mortuary practices in the pottery neolithic
Includes bibliographical references (p. 96-112) and index . - 10-stellige ISBN nicht aus dem Buch
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Neolithic period -- Middle East; Funeral rites and ceremonies, Ancient -- Middle East; Burial -- Middle East -- History; Excavations (archaeology) -- Middle East; Middle East -- Antiquities